Effect of silicification on the water sorption properties of microcrystalline cellulose II - John Rojas Camargo; Carlos Andrés Ortiz Garcia (Universidade de São Paulo, 2011)
The aim of this study was to investigate the water sorption behavior of cellulose II:SiO2 composites and to determine the influence of silicification on this property. These composites were prepared by spray-drying at a cellulose II:SiO2 ratio of 98:2, 95:5, 90:10 and 80:20. The nonlinear models of Guggenheim-Anderson-de Boer (GAB), Generalized D'Arcy and Watt (GDW) and Hailwood & Horrobin (HH), were used for the characterization and analysis of the isotherms. The infrared and powder X-rays characterization showed no signs of chemical modification or change in the polymorphic form of cellulose II by SiO2. The parameters derived from these models indicated that only a 20% level of silicification was able to hinder the water sorption properties of cellulose. Silicon dioxide was the most hydrophobic material since it had a lower ability to form hydrogen bonds with water than cellulose II. This finding was reflected in a delayed compact disintegration time when high levels of silicification (20%) and compression pressures higher than 120 MPa were used. O objetivo deste estudo é investigar o comportamento de sorção de água a partir de misturas de celulose II e SiO2 e determinar a influência da silicificação nesse processo. Estas misturas foram preparadas por nebulização (spray-drying) usando misturas de celulose II e SiO2 nas proporções de 98:2, 95:5, 90:10 e 80:20. Os modelos não-lineares de Guggenheim-Anderson-de Boer (GAB), "Generalized" D'Arcy e Watt (GDW) e Hailwood & Horrobin (HH) foram utilizados para caracterização e análise das isotermas. As misturas foram caracterizadas por infravermelho e raio-X e os resultados não mostraram indicativo de modificação química ou polimórfica da celulose II em combinação com SiO2. Os parâmetros derivados desses modelos indicaram que as propriedades de sorção de água da celulose foram prejudicadas apenas quando empregado um nível de silicificação de 20%. O dióxido de silício foi o material mais hidrofóbico, provavelmente por possuir uma menor capacidade de formar pontes de hidrogênio com a água quando comparado com a celulose II. Este resultado foi refletido em redução no tempo de desintegração, especialmente quando altos níveis de silicificação (20%) e força de compressão (acima de 120 Mpa) foram utilizados.